Unity In Diversity: The Psychological Role of Teamwork in Fostering Compassion and Broadening Perspective in Christian Leadership - Kevin Thomas Marlietama; Janto Chandra; Warren Chandra (Universitas Ahmad Dahlan, 2026)
This study examined the role of high-intensity teamwork experiences in fostering compassion and perspective-taking among emerging Christian leaders. Although teamwork is frequently emphasized in Christian ministry formation, the psychological processes through which collaborative experiences shape leader character remain insufficiently examined. Using a convergent parallel mixed-methods design, data were collected from 186 emerging Christian leaders aged 22–35 years from five Protestant seminaries and Bible schools in Central Java. Quantitative data were obtained using measures of dispositional compassion, perspective-taking, and team experience quality, while qualitative data were gathered through semi-structured interviews with 24 purposively selected participants. Quantitative findings showed that high-quality teamwork experiences significantly predicted compassion (β = .61, p < .001) and perspective-taking (β = .55, p < .001). Shared vulnerability and conflict-resolution experience also emerged as significant mediating processes. Qualitative analysis identified three themes: encountering others through collaborative failure, spiritual accountability in relational growth, and exposure to diversity as a broadener of theological and interpersonal perspective. Integrated findings suggest that structured teamwork experiences may serve as an important psycho-spiritual context for cultivating compassionate and perspective-oriented Christian leadership. The findings highlight the need for seminaries and ministry-training institutions to design collaborative formation experiences that combine responsibility, diversity, reflection, and relational accountability.